Investigation on Typical Cases of the Ground Information Port Based on Cloud Service - Jinjie WANG (天地一体化信息网络)
As a pioneer part of the major project of space-integrated-ground information network (SIGN), the typical application services provided by the ground information port (GIP) are the basic starting point and footing point for the implementation of major project to serve our national strategy and economic construction.Based on the basic framework of the ground information port and the idea of cloud service construction, the typical case of the ground information port was explored, providing reference for the development of the related technical services in the ground information port.